2012
DOI: 10.1073/pnas.1112965109
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and drought in New South Wales, Australia, 1970–2007

Abstract: There is concern in Australia that droughts substantially increase the incidence of suicide in rural populations, particularly among male farmers and their families. We investigated this possibility for the state of New South Wales (NSW), Australia between 1970 and 2007, analyzing data on suicides with a previously established climatic drought index. Using a generalized additive model that controlled for season, region, and long-term suicide trends, we found an increased relative risk of suicide of 15% (95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
176
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(196 citation statements)
references
References 28 publications
5
176
2
Order By: Relevance
“…54,55 Over the 12 years of this longitudinal prospective study, drought was not associated with poorer mental health in mid-aged women in general, or in groups of potentially vulnerable women. The finding that, compared with men, women were at reduced relative risk of suicide during drought 13 suggests that rural women appear to be less affected by drought than rural men. As with all epidemiological studies, the findings relate to average effects and so may not hold true for individual women, whose mental health may be affected by drought.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…54,55 Over the 12 years of this longitudinal prospective study, drought was not associated with poorer mental health in mid-aged women in general, or in groups of potentially vulnerable women. The finding that, compared with men, women were at reduced relative risk of suicide during drought 13 suggests that rural women appear to be less affected by drought than rural men. As with all epidemiological studies, the findings relate to average effects and so may not hold true for individual women, whose mental health may be affected by drought.…”
Section: Discussionmentioning
confidence: 81%
“…16 Furthermore, a large New South Wales study found an increased relative risk of suicide for 10-49 year old rural males with increasing drought, but not for females or older males. 13 These findings suggest that rural women are less affected by drought than men, providing hope that identifying factors that keep women healthy could inform prevention interventions for men in drought-affected communities.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the increasing requirement for women to work in other paid positions away from the farm has been identified as causing feelings of inadequacy, and therefore psychological distress, in older males. In addition, the increasing unpredictability of climate patterns leading to long periods of drought and/or unseasonal flooding have had an impact on the psychological state of rural communities 10,11,39 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been scores of farmer suicides due to losses caused by drought and associated problems in different States of India [3,4]. A link between drought and suicides has been established in Australia [5], Africa, and in the South America. Thus as a trait, drought resistance has immense value to the individual farmer and the society.…”
Section: Introductionmentioning
confidence: 99%